The influences of teachers' work in Rio de Janeiro's municipal schools on their mental health (Research, Society and Development, 2020)
This research sought to understand how teaching is related to the teacher’s mental health. This is an exploratory descriptive study developed in two municipal elementary schools, in a county of Rio de Janeiro’s metropolitan region. A semi-structured interview was carried out, with a previously prepared script and a guiding question. Data analysis was obtained based on Bardin’s content analysis (2011), with the responses being divided into categories. Ten teachers took part in this study. The results showed that teaching and school routine have characteristics that can directly affect teachers’ well-being and influence their mental health, triggering psychic suffering as: stress, tiredness, fatigue, anguish and despair. It was also evidenced that the interferences of a lack of family participation in the student’s human and academic development have a direct influence on dynamics within the school. It was found that it is important to reflect on this subject, because this current phenomenon can affect the teacher’s well-being and its mental health, generating cases of absenteeism and leave from work.